2019
DOI: 10.1029/2019gl083301
|View full text |Cite
|
Sign up to set email alerts
|

MMS Study of the Structure of Ion‐Scale Flux Ropes in the Earth's Cross‐Tail Current Sheet

Abstract: This study analyzes 25 ion‐scale flux ropes in the Magnetospheric Multiscale (MMS) observations to determine their structures. The high temporal and spatial resolution MMS measurements enable the application of multispacecraft techniques to ion‐scale flux ropes. Flux ropes are identified as quasi‐one‐dimensional (quasi‐1‐D) when they retain the features of reconnecting current sheets; that is, the magnetic field gradient is predominantly northward or southward, and quasi‐2‐D when they exhibit circular cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 55 publications
5
41
0
Order By: Relevance
“…Due to the presence of helical structure inside the flux rope, the local radius of curvature of the magnetic field lines increases from 300 to 1,000 km inside the flux rope (Figure 2(c)), which is obtained by magnetic field rotation analysis (Shen et al, 2007). The observational features of the magnetic field, current density, and radius of curvature of the magnetic field lines listed above are consistent with the previous work on flux ropes (e.g., Russell & Elphic, 1979;Slavin et al, 2003;Shen et al, 2007;Zong et al, 2004;Sun et al, 2019).…”
Section: 1029/2019gl085933supporting
confidence: 89%
“…Due to the presence of helical structure inside the flux rope, the local radius of curvature of the magnetic field lines increases from 300 to 1,000 km inside the flux rope (Figure 2(c)), which is obtained by magnetic field rotation analysis (Shen et al, 2007). The observational features of the magnetic field, current density, and radius of curvature of the magnetic field lines listed above are consistent with the previous work on flux ropes (e.g., Russell & Elphic, 1979;Slavin et al, 2003;Shen et al, 2007;Zong et al, 2004;Sun et al, 2019).…”
Section: 1029/2019gl085933supporting
confidence: 89%
“…Similar events have also been reported in simulations (Haynes et al, 2015; Roytershteyn et al, 2015) and observations (Huang SY et al, 2017a, b). These structures, including recently reported kinetic‐scale flux ropes (Huang SY et al, 2016; Matsui et al, 2019; Sun WJ et al, 2019; Wang SM et al, 2019; Yao ST et al, 2020b) and kinetic‐scale magnetic dips and peaks (Hellinger and Štverák, 2018; Stawarz et al, 2018; Yao ST et al, 2018a; Hoilijoki et al, 2019), are new types of coherent structures found in turbulent plasmas, and play important roles in the cascade of turbulence from ion to electron scales (e.g., Huang J et al, 2019; Lucek et al, 2005; Karimabadi et al, 2014; Sahraoui et al, 2020; Shang WS et al, 2020). Yao ST et al (2019a) found that these KSMHs are coupled with electron cyclotron waves, electrostatic solitary waves, and whistler mode waves (Li Z et al, 2019).…”
Section: Introductionmentioning
confidence: 78%
“…The mean Φ FTE was ~0.028 MWb for both showers (Figure 1o), which is comparable to the values obtained in previous studies of Mercury's dayside FTEs (see, Slavin, Lepping, et al, 2010). We could satisfactorily model only a fraction of FTE‐type FRs, which could imply that many of them were in their early stages and still contained enough plasma to affect their structure (see also Priest, 1990; Sun et al, 2019). The mean duration of magnetic flux loading‐unloading event is determined to be 212 s with the loading duration of 115 s ( T load ) (e.g., Imber & Slavin, 2017; Slavin, Anderson, et al, 2010; Sun et al, 2015).…”
Section: Flux Transfer Event Showersmentioning
confidence: 99%